Some animal protein antigens identified in cells of two plant species - Sahin, Ibrahim; Eroksuz, Yesari; Ugur, Kader; Incili, Canan Akdeniz; Eroksuz, Hatice; Aydin, Gizem Nur; Aydin, Suleyman (Walter de Gruyter Gmbh, 2024)
Objectives It has been recently reported that immune activity of some animal peptides/proteins has been found in some plants. In this study, the presence of immune reactivity of alarin, asprosin, paraoxonase, elabela, glucagon, and nesfatin-1 like molecules was investigated in two plant species related to Kastamonu Ta & scedil;k & ouml;pr & uuml; garlic (an endemic cultivar of the Allium sativum L.) and Tunceli garlic (Allium tuncelianum).Methods 10 Kastamonu and 10 Tunceli garlic were embedded in paraffin blocks and 4-5 mu m transversal and longitudinal sections were taken and stained by immunohistochemical method. In addition, 500 mg of wet tissue samples were homogenized from these garlic and supernatants were obtained. The amounts of alarin, asprosin, elabela, glucagon and nesfatin-1 were studied by enzyme linked immunosorbent assay (ELISA) method and paraoxonase was studied by spectrophotometric method.Results Studied molecules show immune reactivity in the cytoplasm of the bulb storage cells of the plants parenchyma. The ELISA supernatant results also confirmed the presence of these animal molecules in the plants.Conclusions Although we cannot reveal the purpose of the presence of these animal molecules detected in plants with these existing data, we predict that these data will be a source of inspiration in the field of botany, that studies will shift in this direction and that they might contribute to the revision of the evolutionary processes of all living things, especially an ancestor of garlics.
Keywords: alarin; asprosin; elabela; glucagon; nesfatin-1; plant cells